PENERAPANlMETODE COOPERATIVElINTEGRATED READING AND COMPOSITIONlUNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KEGIATAN EKONOMI - Murniasih, Putri; Kurnia, Dadang; Sudin, Ali (Jurnal Pena Ilmiah, 2017)
Based on preliminary data in grade fourth SDN Gunungsari. This research is motivated because of the problem on Sosial Science Learning mainly about economic activity lesson. Corrective is done by using cooperative learning method of Cooperative Integrated Reading and Composition (CIRC) type. That refers to the design of Kemmis and Taggart. Preliminary data obtained only 12 students with a complete is 38,70% from 31 students. First cycle the complete student are 15 students with the percentage 51,29%. Second cycle, the complet student are 23 students with the percentage 74,19%, and on third cycle the complete students are 29 students with the percentage 94%. All execution reaches target on third cycle with a target percentage of 85%. Therefore, it can be concluded that application of the CIRC model to the economic activity lesson in the sosial science can improve student learning outcomes.